Serological and Histological Examination of a Nonalcoholic Steatohepatitis Mouse Model Created via the Administration of Monosodium Glutamate. (30th October 2014) - Takai, Atsuko; Kikuchi, Kentaro; Kajiyama, Yusuke; Sugiura, Anna; Negishi, Masatsugu; Tsunashima, Hiromichi; Yamada, Hanae; Matsumoto, Kotaro; Tsuneyama, Koichi; Moritoki, Yuki; Hara, Masumi; Miyakawa, Hiroshi
Abstract : The administration of monosodium glutamate (MSG) to mice induces hepatic steatosis and inflammation. In this study, we investigated the metabolic features of MSG-treated mice and the histological changes that occur in their livers and adipose tissue. MSG mice were prepared by subcutaneously injecting MSG into newborn C57BL/6J male mice. The control mice were subcutaneously injected with saline. Another group of mice was fed a methionine- and choline-deficient diet (MCD). Compared with the control mice, the MSG mice had higher serum levels of insulin and cholesterol than the control mice, whereas the opposite was true for the MCD mice. Microvesicular steatosis and inflammatory cell infiltration were detected in both the MSG and MCD mouse livers. Enlarged adipocytes and crown-like structures were observed in the epididymal fat of the MSG mice, whereas neither of these features was seen in the MCD mice. Flow cytometric analysis revealed increased frequencies of monocytes and M1 macrophages in the livers and epididymal fat tissue of the MSG mice, respectively. The MSG mice exhibited the characteristic liver histopathology of nonalcoholic steatohepatitis (NASH) as well as metabolic syndrome-like features, which suggested that MSG mice are a better model of human NASH than MCD mice.